RPLP1, an NS4B-interacting protein, enhances production of CSFV through promoting translation of viral genome. Issue 1 (31st December 2022) - Zhang, Longxiang; Lin, Jihui; Weng, Maoyang; Wen, Ying; Zhang, Yanming; Deng, Wen
ABSTRACT: Classical swine fever virus (CSFV), the etiological agent of classical swine fever (CSF), causes serious financial losses to the pig industry. Using yeast two-hybrid screening, we have previously identified ribosomal protein RPLP1 as a potential binding partner of CSFV NS4B. In this study, the interaction between host RPLP1 and CSFV NS4B was further characterized by co-immunoprecipitation (co-IP), glutathione S-transferase (GST) pulldown, and confocal microscopy. In addition, lentivirus-mediated shRNA knockdown of RPLP1 drastically attenuated CSFV growth, while stable overexpression of RPLP1 markedly enhanced CSFV production. Moreover, cellular RPLP1 expression was found to be significantly up-regulated along with CSFV infection. Dual-luciferase reporter assay showed that depletion of RPLP1 had no effects on the activity of CSFV internal ribosome entry site (IRES). In the first life cycle of CSFV, further studies revealed that RPLP1 depletion did not influence the intracellular viral RNA abundance but diminished the intracellular and extracellular progeny virus titers as well as the viral E2 protein expression, which indicates that RPLP1 is crucial for CSFV genome translation. In summary, this study demonstrated that RPLP1 interacts with CSFV NS4B and enhances virus production via promoting translation of viral genome.